PENGARUH LATIHAN BOX JUMP TERHADAP POWER OTOT TUNGKAI PADA MAHASISWI KEPELATIHAN OLAHRAGA SEMESTER 6 A ANGKATAN 2013 UNIVERSITAS RIAU - Dian Elfiannara; Slamet '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: From the result of field research during the university study, researcher finds the problem that there is a lack of leg muscles power on sport ladies students in the 6 A semester year 2013. Based on the problem, the researcher gives the training of box jump with three kinds of training: Stride Jump Crossover, Single Leg Stride Jump, and Depth Jump Leap, that can increase the power of leg muscles and gives the training program intensively. The type of this research is experimental research with the research purpose is to see the influence of training. The population of this research is 12 people of sport ladies students in the semester of 6 A year 2013. The sampling technique is total sampling, which the total of population is used as sample. The data collected from pre-test and post-test. The instrument of this research is standing board jump as a tool to measure the leg muscles power. The analysis is conducted by using t-test. Based on data analysis and the discussion, it can be concluded that there is a significant influence of box jump training to the leg muscles power on sport ladies students in the semester of 6 A year 2013 in Riau University that was proven by Tresult 3,715 while Ttable is 1,833. It means Tresult> Ttable. on level of ɑ=0,05.Keyword : Box Jump Exercise2